2014
DOI: 10.1371/journal.pone.0087210
|View full text |Cite|
|
Sign up to set email alerts
|

Chimeric Antibody c.8B6 to O-Acetyl-GD2 Mediates the Same Efficient Anti-Neuroblastoma Effects as Therapeutic ch14.18 Antibody to GD2 without Antibody Induced Allodynia

Abstract: BackgroundAnti-GD2 antibody is a proven therapy for GD2-postive neuroblastoma. Monoclonal antibodies against GD2, such as chimeric mAb ch14.18, have become benchmarks for neuroblastoma therapies. Pain, however, can limit immunotherapy with anti-GD2 therapeutic antibodies like ch14.18. This adverse effect is attributed to acute inflammation via complement activation on GD2-expressing nerves. Thus, new strategies are needed for the development of treatment intensification strategies to improve the outcome of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 44 publications
0
40
0
2
Order By: Relevance
“…The less immunogenic chimeric c.8B6 with a human IgG1 isotype, retains the binding affinity and has been shown to have similar functional properties to ch14.18 both in vitro and in vivo, sharing the same anti-NBL effects but with much less allodynic activity [84]. The lack of OAc-GD2 expression on nerves and the lack of pain associated with c.8B6 provide a rationale for the future clinical application of c.8B6 in high-risk NBL patients.…”
Section: Hu3f8 Mabmentioning
confidence: 99%
“…The less immunogenic chimeric c.8B6 with a human IgG1 isotype, retains the binding affinity and has been shown to have similar functional properties to ch14.18 both in vitro and in vivo, sharing the same anti-NBL effects but with much less allodynic activity [84]. The lack of OAc-GD2 expression on nerves and the lack of pain associated with c.8B6 provide a rationale for the future clinical application of c.8B6 in high-risk NBL patients.…”
Section: Hu3f8 Mabmentioning
confidence: 99%
“…ADCC has been described as one of the effector mechanisms associated with antibodies against tumor-associated gangliosides (Chapman et al, 1990;Fukumoto et al, 1999;Terme et al, 2014;Yamada et al, 2011). It was previously reported that high concentrations of mouse 14F7 mAb were required to induce ADCC in GM3(Neu5Gc)-expressing P3 × 63 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, ADCC is considered as an important clinical mechanism for anti-GD2 immunotherapy [102, 103]. In this respect, anti- O -acetyl-GD2 mAbs seem to be particularly effective as compared to anti-GD2 antibodies in mediating ADCC against O -acetyl-GD2-expressing tumor cells [39, 87, 104]. We also found that anti- O -acetyl-GD2 mAb antibodies induce significant CDC in addition to ADCC in vitro [39].…”
Section: Passive Immunotherapy With Anti-o-acetyl-gd2 Mabsmentioning
confidence: 99%
“…The precise mechanisms by which antibodies specific for O -acetyl-GD2 trigger tumor cell death still require clarification. While they seem to be influenced by O -acetyl-GD2 density at the tumor cell surface, they are also influenced by the antibody isotype [104] similarly to anti-GD2 mAbs [83]. Thus, the proapoptotic activity of anti- O -acetyl-GD2 mAbs cannot be fully explained by their sole antigen recognition activity.…”
Section: Passive Immunotherapy With Anti-o-acetyl-gd2 Mabsmentioning
confidence: 99%
See 1 more Smart Citation